Perils of plutonium [spent nuclear fuel storage]. - Predd, P.P (IEEE spectrum)
This paper focuses on the security of the ponds at reactor sites where radioactive spent fuel are being stored. A recent report by a panel of the National Academy of Sciences in Washington, DC, said that attacks by knowledgeable terrorists with access to appropriate technical means are possible. Such an attack could partly or completely drain a pool, so that the fuel would ignite, resulting in the release of large quantities of radioactive materials to the environment. The US Nuclear Regulatory Commission conceded to the advisability of further analysis but claimed that spent fuel is better protected today more than ever.